Using social proof signs to affect the littering behavior of students using gazebos in a local Manila University - Christian Jerome G. Carlos. 4 0 16; 5 (2019)
u
Thesis:(B.S. Psychology)- Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2